MMA and the conquest of taste: media disputes and seductions (Research, Society and Development, 2021)
When analyzing the history of human society, sports practices have always been present, mixing and mixing with cultures and societies around the world. Among such practices, fights have always gained great prominence, having been used not only for self-defense or health promotion, but also as a political tool for the entertainment of the population, strongly integrating the so-called “politics of the culture of bread and circus”. Already in contemporary times, MMA (Mix Martial Arts) has gained great media attention in recent years, having become a media tool for spectacularization, entertainment and even popular alienation. Thus, television, digital and printed media have made use of MMA as a form of deconstruction and reconstruction of popular taste. From this perspective, this study presented here in the form of an academic essay aimed to focus and critically reflect on MMA and the conquest of taste through media manipulations, supported by the thoughts of Guy Debord.